Evaluating the efficacy of small‐scale marine protected areas for preserving reef health: A case study applying emerging monitoring technology - Bayley, Daniel T.I.; Mogg, Andrew O.M.; Purvis, Andy; Koldewey, Heather J. (Aquatic conservation, 2019)
Marine protected areas (MPAs) are widely used as management tools to conserve species and ecosystems at risk from human impact. Coastal managers often focus MPA designation on biogenic reef environments due to their value and sensitivity to damage. However, difficulties in enforcement and a lack of capacity to adequately monitor MPAs often make it hard for managers to assess the effectiveness of MPAs, particularly in under‐resourced, low‐income coastal countries. Reef community data were collected at three long‐term managed reserves within the Western Visayas region of the central Philippines in order to assess the state of reef community structure inside and outside of these small‐scale locally managed MPAs. In addition, 3D structural data were captured using recently developed 'Structure from Motion' photogrammetry techniques, demonstrating how multiple quantitative metrics of physical structural complexity and health can be recorded in such analyses. These community‐run MPAs were shown to be effective even when small (10–20 ha). Mean fish biomass density was five times greater within present‐day protected sites, alongside significantly increased levels of fish diversity, richness, and size. No significant structural differences were observed inside and outside of MPAs; however, average reef rugosity, height, and roughness were significantly higher in unfished reefs compared to blast‐fished reefs. Reef substrate complexity, coral composition, and level of management, were also shown to structure fish community assemblages, with the link between reef structure and fish richness/abundance disrupted outside of MPAs. The Structure from Motion technique allows a greater range of quantitative morphometrics to be assessed than traditional methods and at relatively low cost. The technique is rapid, non‐destructive and can be archived, increasing the value of data for managers wishing to quantify reef health and efficiently monitor benthic changes through time. We discuss both the limitations and benefits of this technology's future use.